Effect of Activator Percent on Mechanical, Phases Properties of a Pack–Aluminized Low Alloy Steel - Haffed, Sanaa Abd-alhadi (Al-Nahrain Journal of Science, 2011)
الخلاصة: This study deals to diffusion coating treatment "Cementation" with aluminum in order to study phases and some mechanical properties including Micro hardness, Wear resistance, tensile strength and surface property indicating coating thickness layer. Low alloy steel was selected because it used widely in heat –exchangers and gas turbines so it facing a high mechanical pressures under oxidize and corrosive conditions. The specified specimens were treated with a different activator percent aluminizing pack (0,2,5%) of sodium chloride and under an inert atmosphere of argon gas flow ,to prevent the oxidation of treated samples ,results was illustrate successful of diffusion coating treatment to the all selected percent. That’s a formation of a multi coating layer began from the surface layer ,transforming to interfacial layer and to a low matter diffusion layer , inspection show increment in micro hardness values in surface diffusion coating layer ,and dropping towards core ,this was ensure the diffusion coating mechanism successful. Microstructure images of treated systems ensure the formation of diffusion coating layer in different thickness with activator percent, also an improvement in wear resistance occurred and attributed to creation of aluminum phases with a high hardness.